ANALISA ASUHAN KEPERAWATAN INTERVENSI PURSED LIPS BREATHING DENGAN POSISI SEMI FOWLER UNTUK MENINGKATKAN SATURASI OKSIGEN PADA PENDERITA TUBERKULOSIS DI IGD ISOLASI RSUD KISA DEPOK - Mella Mahardika (2023)
Pulmonary TB is the single highest risk factor for infectious agents causing death worldwide. The incidence of Tuberculosis continues to increase due to unfinished treatment factors, drug resistance, weak immunity along with an increase in HIV/AIDS cases. Pulmonary TB patients experience prolonged symptoms so that lung tissue is damaged and disturbed which causes a decrease in oxygen saturation, so respiratory muscle training is needed, one of which is Pursed Lips Breathing by providing a position that helps to facilitate the respiratory muscles to expand properly, namely Semi Fowler. The implementation of this activity is to determine the effectiveness of the Pursed lips breathing intervention with the Semi Fowler Position on increasing oxygen saturation in TB patients in the emergency room. After performing the Pursed lips breathing intervention with the semi fowler position by not using oxygen for approximately 2 minutes with a frequency of two times at different times, it shows that there is an average saturation increase of 1% in managed and resume cases. Based on the analysis of the innovation intervention, it can be concluded that Pursed lips breathing therapy with the Semi Fowler Position provides significant changes in oxygen saturation in patients with Pulmonary TB.